Social–emotional skills of teachers: Mapping the content space and defining taxonomy requirements - Scheirlinckx, Joyce; Van Raemdonck, Lisa; Abrahams, Loes; Teixeira, Karen Cristine; Alves, Gisele; Primi, Ricardo; John, Oliver P.; De Fruyt, Filip (Frontiers in Education, 2023)
Many studies acknowledge the importance of social-emotional skills (SEMS) to function in contemporary society. Understanding these skills and how these develop presents several conceptual and methodological challenges, with emerging consensus on what kind of skills should be fostered in education. Less work, however, has considered SEMS specifically for teachers, despite the fact that they are presumed to be the primary agents to affect SEMS of students. The current article examines different conceptualizations of teacher SEMS and provides a first attempt at defining and structuring this broad conceptual space. We further propose a conceptual teacher SEMS framework that may serve as a basis for an empirical one to guide future educational research and policy-making.